The Consequences of comprising politics : The United States and the Arab Countries of the Middle East - Zandani, Ahmed Abdul Wahid (IIUM Press, 2009)

(untitled)
This book discusses the policies of several core states of the Arab regional system, Syria, Egypt and Saudi Arabia, during 2001 and 2005, that were spurred by the demands and suggestions emphasized in the political discourse of George W. Bush, the President of the United States during the period of the investigation. This study attempts to explain the variations in the Arab states’ foreign policies via the structuralist approach. The findings of the study show that the demands and suggestions of President George W. Bush revolved around three main issues: waging war on “terrorism,” applying liberal democracy and liberal economy. The policies of the selected cases demonstrate that the Arab regional system was being highly penetrated by the United States. These countries dealt with Bush’s demands with a different set of priorities. This, however, enabled the United States to push up its strategy and spawned unprecedented changes in the selected Arab states’ internal and external policies, though in different degrees. The Syrian policies conducted in the context of Arab nationalism and the changes made to satisfy Bush’s demands were confined to achieve its national interests irrespective of the interests of the Arab regional system. The Egyptian and the Saudi policies, to a great extent, were based on their undivided desire to preserve their collaboration with the United States. Accordingly, both of them collaborated with the United States by applying Bush’s demands except those that directly affect the survival of their regimes. On the other hand, the findings showed that the selected states were unable to fully respond to the Bush’s demands due to domestic pressures. Therefore, the selected states opted to maneuver as they reluctantly responded to Bush’s demands.